EPIDEMIOLOGY OF TRAUMATIC BRAIN INJURY (Modern education and development, 2025)
: Traumatic brain injury (TBI) is one of the most important complex multidisciplinary problems in the field of health care. This article provides information on the modern principles of traumatic brain injury. The review examines in detail the epidemiology, pathogenesis, and mechanisms of neurological complications after trauma.